Apoptotic effects of insect tea in HepG2 human hepatoma cells. Issue 2 (2nd April 2016) - Suo, Huayi; Sun, Peng; Wang, Cun; Peng, Deguang; Zhao, Xin
Abstract : Insect tea is a traditional and special tea in China. After the HepG2 cancer cells were treated with insect tea ethanol extracts (ITEE) for 48 h, HepG2 cell proliferation was inhibited, with 40, 80 and 160 μg/mL of ITEE showing inhibitory rates of 35.1%, 59.7% and 86.3%, respectively. Compared to the lower concentration, 160 μg/mL ITEE significantly induced apoptosis as determined by flow cytometry analysis, which showed the content of sub-G1 cancer cells was 38.8%. By RT-PCR, ITEE induced apoptosis in HepG2 cancer cells by increasing caspase-3, caspase-8, caspase-9, Bax, p53, p21, E2F1, p73 and decreasing Bcl-2, Bcl-xL, HIAP-1 and HIAP-2 mRNA expression levels. Insect tea is rich in polyphenols, caffeine, flavones, vitamin C and amino acids. There were 17 kinds of amino acids in insect tea. The functional components of insect tea induce apoptosis in HepG2 cancer cells. Insect tea is a good functional food by its anticancer effects.